Methodologic implications for rehabilitation research: Differences in heart rate variability introduced by respiration. Issue 12 (12th March 2022) - Solinsky, Ryan; Schleifer, Grant D.; Draghici, Adina E.; Hamner, Jason W.; Taylor, J. Andrew
Abstract: Background: Heart rate variability is a measure of autonomic activity that is growing in popularity as a research outcome. However, despite its increased use, the known effects of respiration on heart rate variability measures are rarely accounted for in rehabilitation medicine research, leading to potential misinterpretation. Objective: To describe the effect that unpaced and paced breathing introduces to heart rate variability measures in a rehabilitation medicine relevant example of individuals with spinal cord injury. Design: Cross‐sectional comparison of heart rate variability during unpaced and paced breathing (0.25 Hz, 15 breaths per minute) within the same individuals during the same lab session. Setting: Academic autonomic physiology laboratory. Interventions: Not applicable. Main Outcome Measures: Mean low frequency (LF) and high frequency (HF) heart rate variability power, percentage of total power derived from the LF spectrum, LF:HF ratio. Results: Fifty‐nine individuals with spinal cord injury completed laboratory assessments using standardized protocols (NCT02139436). In repeated measures within individuals, mean LF power was significantly higher in unpaced breathing compared to paced breathing (1292 vs. 573 ms 2, p < .001). A Bland‐Altman plot demonstrated significant positive proportional bias for LF power when comparing unpaced and paced breathing conditions (R 2 = 0.39). Mean HF power was similar between unpaced and paced breathing conditions, although there were wide positive and negative differences between measures, leading to notable uncertainty when respiratory confounders were not accounted for. The percentages of total power derived from the LF spectrum and the mean LF:HF ratio were both significantly higher for unpaced breathing compared to paced breathing (64 vs. 42%, p < .001; and 3.2 vs. 1.1, p < .001, respectively). Conclusion: Respiration has a significant effect on heart rate variability following spinal cord injury, and not accounting for this has serious consequences for accurate interpretation of unpaced data. Future studies of heart rate variability in rehabilitation medicine should accordingly consider paced breathing.